Покращення динамічних та енергетичних характеристик вібраційних машин з дебалансними збудниками - Силивонюк, Андрій Володимирович (Національний університет "Львівська політехніка", 2014)
У дисертації розглянуто та вирішено наступні науково-прикладні проблеми: проблеми пуску вібромашин з двома збудниками коливань; встановлення режиму вібраційного підтримання обертання; можливість забезпечення бігармонічних законів руху несучого тіла машини за рахунок використання явища самосинхронізації збудників. Показано, що почерговий пуск двигунів дозволяє зменшити амплітуди резонансних коливань, динамічне навантаження та величину пускового струму; використання ефекту вібраційного підтримання обертання може забезпечити роботу машини з одним вимкненим двигуном й відповідно заощадити на електричних втратах. Встановлено умови існування та стійкості режиму протифазного синхронного обертання бігармонічних збудників у протилежних напрямках на несучому тілі з трьома ступенями вільності; продемонстровано високу стабільність такого режиму. Проведено чисельне моделювання: пускових режимів вібромашини з двома збудниками; встановлення режимів вібраційного підтримання обертання одного із збудників та явища самосинхронізації бігармонічних збудників на несучому тілі з трьома ступенями вільності. Експериментально перевірено основні теоретичні результати дисертаційної роботи. В диссертации рассмотрены и решаются следующие научно-прикладные проблемы: проблемы пуска вибромашин с двумя возбудителями колебаний; установление режима вибрационного поддержания вращения; возможность обеспечения бигармонических законов движения несущего тела машины за счет использования явления самосинхронизации возбудителей. Показано, что последовательный пуск двигателей позволяет уменьшить амплитуды резонансных колебаний, динамическую нагрузку и величину пускового тока; что использование эффекта вибрационного поддержания вращения может обеспечить работу машины с одним выключенным двигателем и соответственно сэкономить на электрических потерях. Установлены условия существования и устойчивости режима противофазного синхронного вращения бигармонических возбудителей в противоположных направлениях на несущем теле с тремя степенями свободы; продемонстрировано высокую стабильность такого режима. Проведено численное моделирование с учетом динамической характеристики асинхронного двигателя: пусковых режимов вибромашины с двумя возбудителями, установление режима вибрационного поддержания вращения одного из возбудителей и явления самосинхронизации бигармонических возбудителей на несущем теле с тремя степенями свободы. Экспериментально проверены основные теоретические результаты диссертационной работы. The aim of the work is an improvement of dynamic performance and energy efficiency of oscillation machines with a few debalance exciters due to the use of self-synchronization phenomenon. Research methods. The equations of motion of oscillating systems built under the scheme of Lagrange equations of the second kind. Theoretical researches are based on application of method of progressive approximations in combination with the method of direct division of motions. The calculations of transient and steady modes of work of oscillation machines were executed by numeral integration of differential equations of motion and equations of the electromagnetic state of asynchronous engine by the Runge Kutta method with the use of mathematical package of Maple, Matlab. The scientific novelty of research consists in further development of theoretical positions of dynamics of vibromachines with self-synchronized debalance exciters. New results are: the first time in an analytical form expressions are got for an oscillation torque (additional dynamic load) in the zone of resonance for vibromachines with two debalance exciters mounted on the carrier body with one and three degrees of freedom; equations of relative oscillations of speed of rotors of exciters are derived and obtained the formula for the frequency of these oscillations when establishing vibration mode for maintaining rotation for a vibromachine with the flat vibrations of working body; proved the existence of stability of synchronous rotations of two biharmonic exciters that are mounted on the carrier body with three degrees of freedom. Practical value. It is shown that the sequential start of engines allows to reduce the amplitude of the resonant oscillations, the magnitude of the dynamic load and the inrush current, the use of effect of oscillation maintenance of rotation can provide work of machine with one engine turned off and, accordingly, save on power loss. Results of work. The conditions of existence and stability of the mode of antiphase synchronous rotation of biharmonic exciters in opposite directions on the carrier body with three degrees of freedom are defined; high stability of such mode is shown. Methodology of computer analysis of dynamic processes is realized at vibromachines with two exciters, it opens new possibilities for the effective decision of project and productive tasks related to the estimation sustainability and stability of the synchronous modes of motion, more reasonable choice of constructive and dynamic parameters of machines and drive power. Possibility of getting of biharmonic laws of motion of working body of vibromachine with the use of dynamic connection between exciters is shown. A numeral modeling is conducted: starting modes of vibromachine with two exciters, establishment of the mode of oscillation maintenance of rotation of one of exciters and phenomenon of self-synchronization of biharmonic exciters on the carrier body with three degrees of freedom. Experimentally tested the main theoretical results of the thesis.
Улучшение динамических и энергетических характеристик вибрационных машин с дебалансными возбудителями
Improvement of dynamic characteristics and energetic unbalance vibration machines with exciters
Keywords: вібраційна машина; дебалансний віброзбудник; вібраційний момент; самосинхронізація; бігармонічний режим; вібраційне підтримання обертання; вибрационная машина; дебалансный вибровозбудитель; вибрационный момент; самосинхронизация; бигармонический режим; вибрационное поддержание вращения; oscillation machine; unbalance exciter; oscillation moment; selfsynchronization; biharmonic mode; oscillation maintenance of rotation